Systematic review of value-added recycling strategies in coffee processing - Guerrero Echave, Diego Andre; Vera Vilcherrez, Juanita María; Pingo Lozada, José Felix; García Sanchez, Ingrid Estefani (LACCEI, 2025)
The coffee industry generates high volumes of waste in its production operations; therefore, the circular economy represents a promising alternative for managing and adding value to the waste generated. The objective of this review is to identify value-added strategies (upcycling) used to reuse waste produced by the coffee industry. To this end, a descriptive method was used, the PICO strategy for article searches, and the PRISMA method for selection in indexed databases, resulting in 32 articles on various value-added strategies for certain waste products from coffee production. The findings of this research show that spent coffee grounds (SCG) are primarily reused for biofuel, activated carbon, construction components, and fertilizers; while coffee husks show potential for treating soil and water. Furthermore, roasting stands out for its effectiveness in producing energy derived from SCG, as does phosphoric acid to enhance carbon activation. It is possible to affirm that strategies for the value-added reuse of waste reduce negative impacts on the environment and provide valuable sustainable approaches for the coffee industry.